2017
DOI: 10.1016/j.oraloncology.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities and molecular landscape of metastasizing mucinous salivary adenocarcinoma

Abstract: Background Mucinous adenocarcinoma of the salivary gland (MAC) is a lethal cancer with unknown molecular etiology and a high propensity to lymph node metastasis. Mostly due to its orphan status, MAC remains one of the least explored cancers that lacks cell lines and mouse models that could help translational and pre-clinical studies. Surgery with or without radiation remains the only treatment modality but poor overall survival (10-year, 44%) underscores the urgent need for mechanism-based therapies. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Three salivary epithelial-derived carcinoma cell lines, A253, RET981, 23,25 and MAC 26 were used. A253 is ATCC cell line (American Type Culture Collection, Manassas, VA) developed from salivary epidermoid carcinoma (squamous-like) and may represent primary mucoepidermoid carcinoma cells.…”
Section: In Vitro Cell Line Studiesmentioning
confidence: 99%
“…Three salivary epithelial-derived carcinoma cell lines, A253, RET981, 23,25 and MAC 26 were used. A253 is ATCC cell line (American Type Culture Collection, Manassas, VA) developed from salivary epidermoid carcinoma (squamous-like) and may represent primary mucoepidermoid carcinoma cells.…”
Section: In Vitro Cell Line Studiesmentioning
confidence: 99%
“…Multiple molecular abnormalities may contribute to aggressive behavior, possibly via the epigenetic regulation of CSCs (32). The present study demonstrated that the expression levels of Ezh2, SUZ12 and EED, which are components of the polycomb-repressive complex 2 (PRC2), were decreased by ZNF750 overexpression.…”
Section: Discussionmentioning
confidence: 52%
“…This system allows the direct study of the human tumour, which as such maintains its original heterogeneity and molecular identity in the implant. This is very useful for the evaluation of the response to therapies, proving to have, therefore, a high value for the drug screenings in the clinic [18,39]. Schuh et al have recently published a systematic review on the translational applicability of this model [19].…”
Section: Pdx Animal Modelsmentioning
confidence: 99%